2015
DOI: 10.1039/c4sc02328e
|View full text |Cite
|
Sign up to set email alerts
|

Developing diazirine-based chemical probes to identify histone modification ‘readers’ and ‘erasers’

Abstract: New chemical tools to ‘trap’ post translational modification (PTM)-mediated protein–protein interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
48
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 29 publications
1
48
0
Order By: Relevance
“…Most ABPs developed for investigation of sirtuins have only been evaluated using recombinant enzymes or with overexpressing cell lines thus far . A notable exception to this is work from Li and co‐workers, who have demonstrated enrichment of endogenous SIRT3 and SIRT5 from HeLa whole cell lysate using probes based on Kac and Kmal, respectively . We show here the first examples of successful pull‐down of endogenous interaction partners for the Kmyr and Kglut posttranslational modifications.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…Most ABPs developed for investigation of sirtuins have only been evaluated using recombinant enzymes or with overexpressing cell lines thus far . A notable exception to this is work from Li and co‐workers, who have demonstrated enrichment of endogenous SIRT3 and SIRT5 from HeLa whole cell lysate using probes based on Kac and Kmal, respectively . We show here the first examples of successful pull‐down of endogenous interaction partners for the Kmyr and Kglut posttranslational modifications.…”
Section: Resultsmentioning
confidence: 89%
“…Previous investigations by Sieber and co‐workers showed that the commonly used benzophenone photo cross‐linker gave rise to high levels of non‐specific binding . Furthermore, Li and co‐workers found that using the diazirine photo cross‐linker „photo‐Leu“ in close proximity to their modified lysine was preferred . In light of this insight regarding the choice and position of photo cross‐linker, as well as preliminary results from our own laboratory (unpublished), we designed the collection of probe sequences outlined in Scheme A.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We first focused on lysine acetylation and malonylation (Table 1, Entry 4). The photoaffinity probes, probe 3 and probe 4 ( Figure 2b), were developed based on H3K9-acetylated (H3K9ac) and H3K9-malonylated (H3K9mal) peptides, respectively [56]. As expected, while probe 3 captured known deacetylases such as Sirt3, probe 4 specifically labeled recombinant and endogenous Sirt5 from human cell lysates, indicating that the photo-cross-linking strategy can be used to trap erasers of these histone PTMs.…”
Section: Photoreacɵve Groupmentioning
confidence: 92%
“…Furthermore, these two probes can specically identify and enrich endogenous Sirt3 and Sirt5, respectively, from complex HeLa S3 lysates, which demonstrated that diazirine-based AfBPs are also useful tools for trapping erasers of histone lysine acylation from a complex biological environment. 201 In brief, this strategy enables applications for both examining interactions between other PTMs and their erasers and revealing unknown cellular mechanisms controlled by sirtuins.…”
mentioning
confidence: 99%